Assessment of the single point uncertainty of dimensional CT measurements - Fleßner, Matthias; Müller, Andreas; Götz, Daniela; Helmecke, Eric; Hausotte, Tino (NDT.net issue Vol.21 No.02, 2016)
A method analysing the local variations of a series of CT measurements to determine the single point noise is presented. Using a realistic simulation model of the CT system, the mean local offset and the single point uncertainty can additionally be estimated. The method is tested on a measurement series of a micropart. It is shown that the method is capable of identifying areas of increased uncertainty caused by artefacts and of quantifying the value of the single point uncertainty. Additionally, the method is validated using an existing method that is capable of assessing the local quality of a CT measuremen
Keywords: computed tomography; dimensional metrology; single point noise; systematic offset; single point uncertainty; uncertainty mapping; error sources; simulation; artefacts

Automated detection of artefacts for computed tomography in dimensional metrology - Fleßner, Matthias; Müller, Andreas; Helmecke, Eric; Hausotte, Tino (Digital Industrial Radiology and Computed Tomography, 2015)
Artefacts within CT volume data have a large impact on the results of dimensional measurements. To avoid measurement deviations, it is therefore crucial to identify regions affected by artefacts. The presented method analyses the volume data in the proximity of an extracted surface point to calculate a Local Quality Value (LQV). Using this method, surface points affected by artefacts are identified and highlighted in 2D and 3D visualisations. As only the volume data and the extracted surface are required to calculate the LQV, no additional knowledge like a CAD model or a reference measurement is necessary and the analysis can be carried out automatically. CT scans of calibrated gauges blocks that exhibit large errors in the segmented surface dataset due to artefacts are used to demonstrate the capability of the presented method. It is shown that it is possible to increase the accuracy of dimensional measurements by considering the information provided by the LQV.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.lfmt.automa
Keywords: dimensional metrology; computed tomography; artefacts; surface point quality; surface point uncertainty

CT measurements of microparts: Numerical untcertainty determination and structural resolution - Fleßner, Matthias; Blauhöfer, Markus; Helmecke, Eric; Staude, Andreas; Hausotte, Tino (AMA Conferences 2015 - SENSOR 2015 and IRS² 2015, 2015)
Numerical uncertainty determination for X-ray computed tomography (X-ray CT or CT) measurements is a topic of recent research. For this approach, a realistic model of the real CT system within a simulation tool is prerequisite. Therefore, all relevant properties of the CT system, including all significant error sources, have to be modelled realistically within a Virtual Metrological CT (VMCT). For dimensional measurements of microparts, the structural resolution has a strong influence on the measurement result. It is mainly induced by the finite size of the X-ray focal spot and the detector unsharpness. These effects superimpose within the 2D projection data. By examining projection data acquired at varying geometrical magnification and varying tube power, it is possible to separate these error sources and adjust the VMCT accordingly. For a reliable determination of measurement uncertainty, a verification of the VMCT is necessary. As the final measurement results are derived from the extracted surface data, it is favourable to examine characteristics of the surface data instead of characteristics of the projection or volume data. A possible approach is to use an Aperiodic Spatial Frequency Standard (ASFS) to determine the structural resolution of the real and simulated CT system. The ASFS allows comparing the structural resolution for a variety of sensors by investigating the frequency response of the sensor on geometrical structures of different spatial frequency. This is demonstrated on measurements of an ASFS with four different sensors (CT, fringe projection, stylus profilometer, chromatic aberration probe).
UnivIS-Import:2015-07-08:Pub.2015.tech.FT.lfmt.ctmeas
Keywords: dimensional metrology; computed tomography; microparts; numerical uncertainty determination; structural resolution

Determination of metrological structural resolution of a CT system using the frequency response on surface structures - Fleßner, Matthias; Vujaklija, Nemanja; Helmecke, Eric; Hausotte, Tino (PTB open access repository, 2015)
A novel method for the determination of the structural resolution of a computed tomography (CT) system is presented. The method uses the frequency response of the CT system while measuring the surface of an Aperiodic Spatial Frequency Standard (ASFS). The geometry of the standard allows it to investigate a broader range of possible structural resolutions using just one standard. Simulations and experiments, using CT with different acquisition parameters and a fringe projection system, show that the method is a promising alternative for determining the structural resolution of a measurement system.
UnivIS-Import:2015-04-17:Pub.2015.tech.FT.lfmt.determ
Keywords: Dimensional metrology; computed tomography; structural resolution; frequency response

Dimensional Measurements with X-ray Computed Tomography: Methods of Measurement Uncertainty Determination - Fleßner, Matthias; Helmecke, Eric; Hausotte, Tino (euspen Micro/Nano Manufacturing Workshop 2015, 2015)

Error sources and numerical uncertainty determination for CT measurements of microparts - Hausotte, Tino; Fleßner, Matthias; Helmecke, Eric; Staude, Andreas (Meeting of CIRP CWG MicroPE, 2014)

Evaluating and visualizing the quality of surface points determined from computed tomography volume data - Fleßner, Matthias; Müller, Andreas; Helmecke, Eric; Hausotte, Tino (PTB open access repository, 2015)
By evaluating the volume data in the proximity of a surface point, a Local Quality Value (LQV) is calculated for each surface point of a Computed Tomography (CT) measurement. This allows an automatic and reliable identification of areas containing surface points with reduced accuracy. A colour-coded visualisation of the LQV allows a highlighted display of untrustworthy measurement data. This method is capable of identifying a broad range of artefacts (including beam hardening, noise and rounded off edges) and of points of reduced accuracy due to the fixture of the part on the rotational stage.
UnivIS-Import:2015-04-17:Pub.2015.tech.FT.lfmt.evalua
Keywords: Dimensional metrology; computed tomography; artifacts; surface determination; surface point quality; surface point uncertainty

Industrielle Computertomographie in der dimensionellen Messtechnik - Fleßner, Matthias; Helmecke, Eric; Hausotte, Tino (6. SWISSMEM SEMINAR Dimensionelle Messtechnik in der Praxis, 2015)

Influence of error sources on measurement deviations of dimensional CT measurements by using a full factorial design of experiments - Zippert, Patrick; Jung, Ruedi; Fleßner, Matthias; Helmecke, Eric; Hausotte, Tino (7th Conference on Industrial Computed Tomography (iCT 2017), 2017)

Numerical measurement uncertainty determination for computed tomography in dimensional metrology - Helmecke, Eric; Fleßner, Matthias; Gröschl, Andreas Christian; Staude, Andreas; Hausotte, Tino (Proceedings of the 21st IMEKO Word Congress, 2015)
In Computed Tomography (CT) in dimensional metrology, the numerous complex measurement process steps with various influences present a significant impact on the measurement results. For the determination of measurement uncertainty, it is therefore important to consider all of these influences. The paper discusses the possibilities of a promising approach, the numerical uncertainty determination for CT in dimensional metrology.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.lfmt.numeri
Keywords: computed tomography; dimensional metrology; standardization; numerical uncertainty determination; simulation

Optische Sensoren im Vergleich zu taktil-optischen Sensoren und zu Computertomografie - Schmidt, Ingomar; Fleßner, Matthias (Tagungsband zur Form- und Konturmesstechnik 2013, 2013)
Klassische Formprüf- und Konturmessgeräte basieren auf der taktilen Antastung der Objektoberfläche. Zunehmend werden Form- und Konturmessungen aber auch mit Koordinatenmessgeräten durchgeführt. Hierbei steht eine hohe Flexibilität, insbesondere durch den Einsatz unterschiedlicher Sensoren und vergrößerter Messbereiche zur Verfügung. Neben optischen und taktil-optischen Sensoren kommen dabei auch computertomografische Sensoren zum Einsatz. Die Einsatzgebiete und Anwendungsbereiche der unterschiedlichen Sensoren werden verglichen. Am Beispiel der Messung eines Mikrokonturnormals wird gezeigt, dass mit Computertomografie genaue Ergebnisse auch an Mikrostrukturen erzielt werden.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.lfmt.optisc

SLS unter die Lupe genommen - Eine Analyse der Genauigkeit von selektiven Lasersinterprozessen - Loderer, Andreas; Fleßner, Matthias; Galovskyi, Bogdan; Hausotte, Tino (wt Werkstattstechnik - Online, 2015)
UnivIS-Import:2015-04-02:Pub.2015.tech.FT.lfmt.slsunt

Systematic form deviations of additive manufactured parts - methods of their identification and correction - Galovskyi, Bogdan; Fleßner, Matthias; Loderer, Andreas; Hausotte, Tino (Abstracts of the ISMQC 2013, 2013)
Additive manufacturing becomes more widespread nowadays. Selective laser sintering (SLS) as one of the additive manufacturing methods has a high potential because of a wide range of raw materials. In most cases the accuracy of a SLS process depends on the scanner system of the manufacturing laser beam, parameters of the laser beam and working distance. In order to meet higher quality parameters and to provide manufacturing defects correction a measurement system should be integrated in the process. A measurement system should be developed with considering harsh conditions in the process chamber and taking into account features of the measurement object. Thus only non-contact sensors could be applied. Measurement systems based on the photogrammetric principle are more applicable for such tasks. In current paper presented the investigation which was conducted to determine optical compatibility of the measurement system with raw materials. Measurements were carried out with materials heated to an operating temperature and after a melting process. Also, the test samples of different shape were produced with the SLSMachine. The influence of the manufacturing angle was investigated. General recommendations about the compensation of this influence and for location of an object in the powder bed were formulated. This paper presents some research results necessary for detection and prevention of errors during the SLS process. It is an important experience for application and integration of a measurement system as a monitoring instrument during the SLS process.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.lfmt.system
Keywords: Form deviation; Measurement system; SLS

Uncertainty of Dimensional Measurements using Computed Tomography - Fleßner, Matthias; Helmecke, Eric; Hausotte, Tino (XCT-Seminar, 2014)